In vivo blood metal ion levels in patients after total shoulder arthroplasty - Reiner, Tobias; Bader, Nina; Panzram, Benjamin; Bülhoff, Matthias; Omlor, Georg; Kretzer, Jan Philippe; Zeifang, Felix (Journal of shoulder and elbow surgery, 2019)
Background - Products from metal wear have been identified as a potential cause of adverse local tissue reactions and implant failure in total hip arthroplasty. However, the role of metal ion exposure in patients after total shoulder replacement is unclear. The objective of the present study was to determine in vivo blood metal ion levels of cobalt, chromium, and titanium in patients after anatomic total shoulder arthroplasty (TSA) or reverse TSA. - Methods - A consecutive series of patients after anatomic TSA or reverse TSA was evaluated retrospectively. After exclusion of patients with additional metal implants, 40 patients with unilateral anatomic TSA (n = 20) or reverse TSA (n = 20) were available for whole-blood metal ion analysis at a mean follow-up of 28 ± 9.6 months. Twenty-three healthy individuals without metal implants served as a control group. - Results - Mean cobalt ion concentrations were 0.18 µg/L (range, 0.1-0.66 µg/L), 0.15 µg/L (range, 0.03-0.48 µg/L), and 0.11 µg/L (range, 0.03-0.19 µg/L), mean chromium ion levels were 0.48 µg/L (range, 0.17-2.41 µg/L), 0.31 µg/L (range, 0.09-1.26 µg/L), and 0.14 µg/L (range, 0.04-0.99 µg/L), and mean titanium ion concentrations were 1.31 µg/L (range, 0.75-4.52 µg/L), 0.84 µg/L (range, 0.1-1.64 µg/L), and 0.62 µg/L (range, 0.32-2.14 µg/L) in the reverse TSA group, the anatomic TSA group, and the control group, respectively. - Conclusions - TSA resulted in elevated metal ion levels compared with healthy controls, although overall metal ion concentrations measured in this study were relatively low. The role of local metal ion exposure in patients with total shoulder replacements should be further investigated.
Available online 3 December 2018
Gesehen am 26.11.2019